2017
DOI: 10.1097/prs.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Medial Superficial Perforator of the Superficial Circumflex Iliac Artery Perforator Flap Using Computed Tomographic Angiography and Surgical Anatomy in 142 Patients

Abstract: Despite the origin of the medial perforator, it was constantly observed penetrating the deep fascia. However, the pathway of the medial perforator can be either anchoring directly into the dermis or extending as an axial pattern artery, implicating a different effect on the survival of the flap. These new findings will allow better understanding for elevating the superficial circumflex iliac artery perforator flap based on the medial perforator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
81
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 18 publications
1
81
3
Order By: Relevance
“…When a long and large skin paddle is required, it is safe to incorporate perforators from the deep branch of the SCIA, which often gives off branches running in the axial direction. This is in accordance with a report by Suh et al, which introduced two types of perforators branching off from the superficial branch of the SCIA: the direct anchoring type and the axial type, the latter enabling longer skin paddles (Suh, Jeong, Choi, & Hong, ). Thus, when employing a chimeric SCIP flap or a large SCIP flap, the deep branch of the SCIA has to be identified and dissected.…”
Section: Discussionsupporting
confidence: 92%
“…When a long and large skin paddle is required, it is safe to incorporate perforators from the deep branch of the SCIA, which often gives off branches running in the axial direction. This is in accordance with a report by Suh et al, which introduced two types of perforators branching off from the superficial branch of the SCIA: the direct anchoring type and the axial type, the latter enabling longer skin paddles (Suh, Jeong, Choi, & Hong, ). Thus, when employing a chimeric SCIP flap or a large SCIP flap, the deep branch of the SCIA has to be identified and dissected.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the above‐mentioned techniques, the SCIP propeller flap allows for a relatively easy and rapid tissue transfer, as the perforator location is consistent (Suh et al, ); it is also located close to the defect site. It is simple to obtain a thin flap (Choi et al, ) and is advantageous for penoscrotal contouring because groin tissue itself is thinner than other areas.…”
Section: Discussionmentioning
confidence: 99%
“…When elevating the SCIP propeller flap based on the medial perforator, some factors need to be taken under consideration. The SCIP pedicle can be divided into axial or anchoring types (Suh et al, ). The axial type is more reliable when designing long flaps because the main pedicle usually extends beyond the ASIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the epidermis is CK19negative. 3 Although a specific chemotherapy regimen has not been established for EMPD with distant metastases, Yoshino et al 4 studied metastatic EMPD treated with monthly docetaxel and reported that the disease control rate was as high as 83%. It is expected that docetaxel therapy will become the first-line chemotherapy for metastatic EMPD in the future.…”
mentioning
confidence: 99%